2017
DOI: 10.3390/rs9111127
|View full text |Cite
|
Sign up to set email alerts
|

On the Spatial and Temporal Sampling Errors of Remotely Sensed Precipitation Products

Abstract: Observation with coarse spatial and temporal sampling can cause large errors in quantification of the amount, intensity, and duration of precipitation events. In this study, the errors resulting from temporal and spatial sampling of precipitation events were quantified and examined using the latest version (V4) of the Global Precipitation Measurement (GPM) mission integrated multi-satellite retrievals for GPM (IMERG), which is available since spring of 2014. Relative mean square error was calculated at 0.1 • ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 12 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Several studies evaluated the uncertainties related to the sampling of precipitation measurements when estimating areal precipitation (Behrangi & Wen, 2017; Tang et al., 2018; Tian et al., 2018; Villarini et al., 2008). Here, the spatial sampling error is estimated by comparing the native resolution Subang radar precipitation (on a 0.0045° grid) against itself, but regridded onto the coarser 0.1° IMERG grid.…”
Section: Validation Of Imerg Precipitation Data Over the MCmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies evaluated the uncertainties related to the sampling of precipitation measurements when estimating areal precipitation (Behrangi & Wen, 2017; Tang et al., 2018; Tian et al., 2018; Villarini et al., 2008). Here, the spatial sampling error is estimated by comparing the native resolution Subang radar precipitation (on a 0.0045° grid) against itself, but regridded onto the coarser 0.1° IMERG grid.…”
Section: Validation Of Imerg Precipitation Data Over the MCmentioning
confidence: 99%
“…However, these studies were subject to potentially large spatial sampling errors, that is, errors incurred when interpolating gauge precipitation data onto the IMERG grid. By degrading the same precipitation product onto different spatio-temporal resolutions, Behrangi and Wen (2017) showed that these errors can be large, especially over land areas. Similarly, Tian et al (2018) and Tang et al (2018) found that rain gauge density has a large impact on IMERG skill metrics over China.…”
mentioning
confidence: 99%
“…The GPM Core Observatory was launched on February 28, 2014 by a joint effort of NASA and the Japan Aerospace Exploration Agency (JAXA). Since then, several studies have examined whether the rainfall products from the GPM mission are capable to accurately estimate global precipitation [8,9,10,11,12] and provide the order of magnitude of discrepancies between observations and satellite products highlighting the reasons for such problems [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal linear combination (OLC) approach (Bishop and Abramowitz, 2013;Hobeichi et al, 2018) provides an analytically optimal linear combination of ensemble members (rainfall estimates in this case) that minimizes the mean square error when compared to a dataset that is assumed to be accurate enough to be considered as a calibration dataset Y REF and thus accounts for both the performance differences and error covariance between the rainfall products. The optimal linear combination is therefore insensitive to the addition of redundant information.…”
Section: The Optimal Linear Combination Approachmentioning
confidence: 99%
“…The integration method we adopted is the optimal linear combination (OLC) approach (Bishop and Abramowitz, 2013;Hobeichi et al, 2018), which is based on a technique that provides an analytically optimal linear combination of rainfall products and accounts for both the performance differences and error covariance between the products. We tested the performance of the product (1) over four key regions, namely, India (IN), the conterminous United States (CONUS), Australia (AU) and Europe (EU), where high-quality ground-based hydrometeorological networks are available, and (2) in Africa and South America by using a triple-collocation (TC) analysis (Stoffelen, 1998).…”
Section: Introductionmentioning
confidence: 99%